The Relationship between Workers’ Emotional Status and Productivity among Academic Staff in Universiti Tun Hussein Onn Malaysia (UTHM) - MOHD ADI, MOHD NAZIR; Mohd Angsor, Mohd Asmadi; Abd Samat, Mohammad Arif (Research in Management of Technology and Business, 2022)
Workers’ productivity is a well-studied area explained in various ways, but the relationship between emotional status and productivity has yet to be thoroughly evaluated. This study investigates the relationship between workers’ emotional status and productivity among academic staff in Universiti Tun Hussein Onn Malaysia (UTHM). The study was conducted in UTHM campus in Parit Raja, Johor. A correlation analysis evaluates emotional status (positive and negative emotions) and workers’ productivity. We used a questionnaire survey approach with a five-point Likert scale to measure the variables of emotional status and productivity. We examine the relationship between emotional states and workers’ productivity. The analysis and result showed that positive emotion had a positive relationship with productivity (r=0.369, p=0.045), and negative emotion had an insignificant negative relationship with productivity (r=-0.237, p=0.207). Such findings suggested that academic staff emotional states must be addressed as part of university operational and management strategy to ensure higher productivity and the mental well-being of academic staff.